2003
DOI: 10.1021/nl025918y
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Maghemite Core−Shell Nanoparticles Using a Sequential Synthesis

Abstract: Pt@Fe 2 O 3 core−shell nanoparticles have been made using a sequential synthetic method. Platinum nanoparticles were synthesized via reduction of platinum acetylacetonate in octyl ether, and layers of iron oxide were subsequently deposited on the surface of Pt nanoparticles through thermal decomposition of iron pentacarbonyl. The core−shell nanoparticles were characterized by powder X-ray diffraction, high-resolution transmission electron microscopy, and X-ray photoemission spectroscopy. Thickness of the shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

37
222
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 412 publications
(261 citation statements)
references
References 44 publications
(86 reference statements)
37
222
1
1
Order By: Relevance
“…Various preparation techniques, such as sequential synthesis and arc discharge, have been proposed for preparation of core-shell structural catalysts [10][11][12][13] . Recently, plasma sputtering deposition has been studied extensively because the technique is feasible and no post-treatment is needed 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Various preparation techniques, such as sequential synthesis and arc discharge, have been proposed for preparation of core-shell structural catalysts [10][11][12][13] . Recently, plasma sputtering deposition has been studied extensively because the technique is feasible and no post-treatment is needed 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously demonstrated that the sequential synthesis of core-shell nanoparticles from molecular precursors is readily achievable [13,14], as heterogeneous nucleation and growth are often favored thermodynamically [15]. The advantage of the sequential method is its ability to deposit one component at a time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a great deal of work has been done in preparing new types of Pt nanomaterials such as shape controlled nanoparticles (Ahmadi et al 1996;Song et al 2004;Lee et al 2008;Peng and Yang 2009;Zhou et al 2009) and supported Pt nanoparticles (Teng et al 2003;Chupas et al 2007;Alonso et al 2008;Joo et al 2009;Shanmugam and Gedanken 2009a), motivated by the need for high catalytic activity. Reducing the consumption of Pt without sacrificing its catalytic performance is an important subject of research due to its high value and limited supply.…”
Section: Introductionmentioning
confidence: 99%